Association of vitamin D and phosphor levels with growth retardation in children with chronic kidney disease - Ariani; Subandiyah Krisni; Hutabarat Priscilla Yoella (Medical Faculty of Brawijaya University, Indonesia, 2022)
Introduction: Growth retardation is a complication often found in children with chronic kidney disease (CKD). Growth retardation is characterized by the failure to reach a child's potential linear growth height. Fifty percent of children with CKD will have a height below the third percentile. The causes of growth retardation in CKD are multifactorial. One of them is the electrolyte balance of phosphorus and lack of vitamin D levels which play a role in the linear growth disorders of children with CKD. This study aims to determine the relationship between vitamin D and phosphorus levels on growth retardation in children with chronic kidney disease. Methods: This observational retrospective analytic study was conducted at the Polyclinic and Inpatient Room of the Department of Pediatrics in Saiful Anwar General Hospital, Malang from June 1, 2021 to September 2021. There were 68 subjects, divided into 2 groups: patients with CKD with growth retardation and without growth retardation, age ranging from 2 -18 years. Univariate test is used to describe the frequency distribution of each variable. The Chi-Square test used determines the correlation of each variable, the Spearman correlation test to see the strength of the relationship between the variables of vitamin D and phosphorus on growth retardation. The significance level and confidence interval were P<0.05 and 95%, respectively. Data were analyzed using SPSS v.26 for windows. Result: We found a correlation between vitamin D levels in patients with chronic kidney disease and growth retardation (P=0.005), as well as a correlation between phosphorus levels in patients with chronic kidney disease and growth retardation (p=0.022).Vitamin D and phosphorus had a correlation coefficients of 0.427, and 0.300 to growth retardation (p<0.05). We also found a significant direct correlation between vitamin D and growth retardation (β= 0.358, p=0.002), which shows a greater effect than the indirect relationship between vitamin D and phosphorus-mediated growth retardation. Conclusion: There is a significant corr between vitamin D level and phosphorus on growth retardation in children with chronic kidney disease.